1996
DOI: 10.1021/ma960413d
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Synthesis of Narrow Molecular Weight Distribution Poly(trimethylvinylsilane) (PTMVS), Polystyrene−PTMVS Block Copolymers, and Poly(phenyldimethylvinylsilane). Conversion of Poly(phenyldimethylvinylsilane) into Poly(fluorodimethylvinylsilane)

Abstract: The anionic polymerizations of trimethylvinylsilane (TMVS) initiated by t-BuLi in toluene at −20 °C and of phenyldimethylvinylsilane (PDMVS) at 0−20 °C proceed in high yields (>95%), giving narrow molecular weight distribution (MWD ≤ 1.15) polymers. Polystyrene−PTMVS AB block copolymers having relatively narrow molecular weight distributions were synthesized by initiation of TMVS by poly(styryllithium). The reaction of poly(phenyldimethylvinylsilane) (PPDMVS) with HBF4·Et2O in toluene at 60 °C resulted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The protodesilylation was performed mainly according to Gan et al12 Thirteen grams of the copolymer (run 3, 0.0043 mol PhSi) was placed in a 500‐mL three‐necked round‐bottom flask with a condenser under an argon atmosphere and dissolved in 200 mL of hot toluene (100–105 °C). The reagent (3 mL of HBF 4 in diethylether, 0.0111 mol) was added slowly through a valve and the reaction was continued for 4 h, after which it was allowed to cool.…”
Section: Methodsmentioning
confidence: 99%
“…The protodesilylation was performed mainly according to Gan et al12 Thirteen grams of the copolymer (run 3, 0.0043 mol PhSi) was placed in a 500‐mL three‐necked round‐bottom flask with a condenser under an argon atmosphere and dissolved in 200 mL of hot toluene (100–105 °C). The reagent (3 mL of HBF 4 in diethylether, 0.0111 mol) was added slowly through a valve and the reaction was continued for 4 h, after which it was allowed to cool.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, depending on the initiator type and polymerization conditions, linear, branched, hyperbranched, and cyclic microstructures are possible for polyethylene (Scheme ). Similar irregular H-transfers resulting in complex microstructures can occur for the anionic polymerizations of some vinyl organosilanes, α-(aminomethyl)­acrylates, and acrylonitriles . In contrast, regioregular isomerizations during propagation are exceedingly rare.…”
Section: Introductionmentioning
confidence: 75%
“…The strategy, which was for the first time proposed by T. E. Hogen-Esch, et al in 1996, 1 had not been realized until we recently demonstrated that copolymers of di(isobutoxy)methylvinylsilane 3 and styrene prepared by radical copolymerization can be transformed into poly[(vinyl alcohol)-co-styrene]s (Scheme 1). 2 In fact, that is the first example of the synthesis of poly [(vinyl alcohol)-co-styrene].…”
mentioning
confidence: 99%